2020
DOI: 10.1037/int0000225
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and effectiveness of a telehealth service delivery model for treating childhood posttraumatic stress: A community-based, open pilot trial of trauma-focused cognitive–behavioral therapy.

Abstract: Telepsychotherapy (also referred to as telehealth or telemental health), the use of videoconferencing to deliver psychotherapy services, offers an innovative way to address significant gaps in access to care and is being used to deliver a variety of treatments for youth. Although recent research has supported the effectiveness of telehealth delivery of a variety of interventions for children, the literature has focused very little on childhood posttraumatic stress disorder. This pilot study examined the feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 46 publications
0
68
1
2
Order By: Relevance
“…2017 77 Case series- Comer et al. 2014 76 -Reductions in anxiety symptoms -comparable improvements in functional outcomes across groups Anxiety Family Based CBT 7–14 Multiple Baseline- Carpenter et al., 2018 78 -Significant proportion were treatment responders -maintained 3 month follow up PCIT CALM for Early Childhood Anxiety 4–8 Case Study- Cooper-Vince et al., 2016 87 -reduction in anxiety symptoms PTSD Trauma Focused CBT (TF-CBT) 7–16 Pilot open trial- Stewart et al., 2017 82 Large community open trial- Stewart et al., 2020 81 -Reduction in PTSD symptoms -feasibility in underserved communities Eating Disorders (Anorexia) Family Based Treatment (FBT) 13–18 Case Series- Anderson et al., 2017 90 -Increases in BMI -decreased eating disorder symptoms Note. CBT = Cognitive Behavioral Therapy, OCD = Obsessive Compulsive Disorder, PTSD = Post-Traumatic Stress Disorder, BMI = Body Mass Index, RCT = randomized controlled trial.…”
Section: Treatment Of Internalizing Disorders Via Telehealthmentioning
confidence: 99%
See 1 more Smart Citation
“…2017 77 Case series- Comer et al. 2014 76 -Reductions in anxiety symptoms -comparable improvements in functional outcomes across groups Anxiety Family Based CBT 7–14 Multiple Baseline- Carpenter et al., 2018 78 -Significant proportion were treatment responders -maintained 3 month follow up PCIT CALM for Early Childhood Anxiety 4–8 Case Study- Cooper-Vince et al., 2016 87 -reduction in anxiety symptoms PTSD Trauma Focused CBT (TF-CBT) 7–16 Pilot open trial- Stewart et al., 2017 82 Large community open trial- Stewart et al., 2020 81 -Reduction in PTSD symptoms -feasibility in underserved communities Eating Disorders (Anorexia) Family Based Treatment (FBT) 13–18 Case Series- Anderson et al., 2017 90 -Increases in BMI -decreased eating disorder symptoms Note. CBT = Cognitive Behavioral Therapy, OCD = Obsessive Compulsive Disorder, PTSD = Post-Traumatic Stress Disorder, BMI = Body Mass Index, RCT = randomized controlled trial.…”
Section: Treatment Of Internalizing Disorders Via Telehealthmentioning
confidence: 99%
“… 80 One large community based open trial of 70 trauma-exposed children demonstrated reduction in PTSD symptoms after receiving telehealth delivered TF-CBT. 81 Telehealth delivered TF-CBT is also supported by smaller open trails 82 and case series documenting its efficacy with Hispanic/Latinx youth. 83…”
Section: Treatment Of Internalizing Disorders Via Telehealthmentioning
confidence: 99%
“…Children and youth were the third most highly-represented priority population identified in the literature (see Table 3 ). Primary research studies indicate that children and youth are already at high risk of poor mental health, with COVID-19 expected to worsen this risk [ 116 ]. In a cross-sectional survey of n = 3613 youth from 20 provinces in China, depression rates of 22.28% were found during the pandemic, compared with pre-pandemic rates of 13.2% [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The relatively lower rates of provider satisfaction and more mixed perceptions of telehealth delivery in our study may not only reflect the inclusion of PHPs, but also the rapid transition to telehealth among all providers necessitated by the COVID-19 pandemic. This rapid transition precluded the types of comprehensive preparation and training that have often preceded the delivery of telehealth interventions reported in other studies, such as training in the use of telehealth platforms and detailed protocols or interactive treatment activities designed specifically for virtual delivery (e.g., Myers et al, 2015;Stewart et al, 2020). While providers in both the outpatient clinic and PHPs received brief trainings in telehealth documentation and billing, they received very little support in how to effectively translate interventions designed for in-person delivery to a telehealth platform in an engaging manner.…”
Section: Discussionmentioning
confidence: 99%